Preliminary Test of the Sensitivity of Colletotrichum spp. to Binahong Ethanol Extract (Anredera cordifolia) - Aminatuzzifah, Putri; Bahri, Syamsul; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The agricultural sector in Indonesia, especially the horticultural subsector, plays an important role in the economy and food security. One of the leading commodities in horticulture is the chilli plant (Capsicum annuum), which is very susceptible to anthracnose disease caused by the fungus Colletotrichum spp. This study aims to test the inhibitory activity of ethanol extract from binahong (Anredera cordifolia) leaves against the growth of Colletotrichum spp. fungus as an alternative environmentally friendly disease control. The research was conducted using a completely randomised design (CRD) with variations in extract concentrations of 0%, 0.5%, 1%, 1.5%, 2%, and 2.5%, each of which was tested three times. The results showed that 2.5% concentration of binahong leaf extract produced the highest inhibitory activity of 70%, while 0.5% concentration showed 56% inhibition. This inhibitory activity was categorised as strong. ANOVA analysis showed significant differences between treatments (p < 0.05). These findings demonstrate the potential of binahong leaf extract as a biofungicide in the control of anthracnose disease in chilli plants, which may contribute to more sustainable and environmentally friendly agricultural practices.